New Developments in the Field of Production and Application of Multi‐Material Wire Arc Additive Manufacturing Components: A Review - Treutler, Kai; Wesling, Volker (Advanced engineering materials, 2025)
It is evident that, due to the inherent process properties, arc‐based additive manufacturing offers the possibility of specifically applying locally different material properties (functional grading). One method of achieving this is to utilize a range of materials. Alternatively, the application of varying energy inputs has been demonstrated to yield different material properties. The scientific community is currently focusing on four core topics regarding multi‐material approaches in wire arc additive manufacturing. Firstly, the anisotropic behavior in the welding direction is presented. Secondly, the potential of employing materials with high plasticity to enhance local strength in components subjected to cyclic loading with locally notched components is a subject of discussion. The third research focus is on the influence of the production sequence on the local properties of surface layers in arc‐based production for specific corrosion and wear protection properties. The fourth and most extensive field pertains to the production of functional graded material systems for a wide range of applications. The present work aims to provide a comprehensive overview of the current state of research in these four research areas, with a view to establishing a connection to potential industrial applications. Moreover, it will furnish researchers with a range of new research perspectives.